Metode Elektrooptis sebagai Pendeteksi Radikal Bebas dan Prospek untuk Evaluasi Total Mutu Minyak Goreng - K Sofjan Firdausi; Heri Sugito; Ria Amitasari; Sri Murni (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
One main problem of standard methods for determination of frying oil quality is various parameter of indicators with their various wide of methods or equipments. In this research we proposed a new method for determination of oil quality using single electrooptics parameter to replace previous indicators. The samples used in the experiment were various conditions of palm oils from the same brand. The level of oil quality was proposed by the value of 2, which represents as the relative number of free radicals produced in the sample. The change of polarization was measured by the value of as the samples were induced by an external electric field using high voltage dc power supply. At room temperature of 28 C electrooptics method seems capable to detect free radicals and to distinguish all kinds of palm oils. This method has an opportunity to provide a single parameter of oil quality and an evaluator of halal or authentic food from fats.